2022
DOI: 10.1007/s10499-021-00821-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet and feeding strategy on the performance of nitrifying trickling filter, oxygen consumption and ammonia excretion of gilthead sea bream (Sparus aurata) raised in recirculating aquaculture systems

Abstract: Gilthead sea bream (Sparus aurata) was raised in six individual recirculating aquaculture systems (RAS) whose biofilters’ performance was analyzed. Fish were fed with three different diets (a control diet, a fishmeal-based diet (FM), and a plant meal-based diet (VM)) and with three different feeding strategies (manual feeding to apparent satiation, automatic feeding with restricted ration, and auto-demand feeding). For every combination of diet and feeding strategy, the mean oxygen consumption, ammonia excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…Alternatively, the lower expression of rhesus glycoproteins may be explained by a reduced ‘peak’ of ammonia in this feeding regime as feed intake is more spread out over the day compared to batch-fed carp. This was previously observed in demand-fed carp and seabream ( van Kessel et al, 2016 ; Godoy-Olmos et al, 2022 ), although not in European eel ( Heinsbroek et al, 2008 ). These results (increased activity of ammonia-producing enzymes and reduced transporter expression) fuel the hypothesis that a larger amount of the ammonia produced by amino acid oxidation is converted to N 2 before being excreted into the surrounding water.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Alternatively, the lower expression of rhesus glycoproteins may be explained by a reduced ‘peak’ of ammonia in this feeding regime as feed intake is more spread out over the day compared to batch-fed carp. This was previously observed in demand-fed carp and seabream ( van Kessel et al, 2016 ; Godoy-Olmos et al, 2022 ), although not in European eel ( Heinsbroek et al, 2008 ). These results (increased activity of ammonia-producing enzymes and reduced transporter expression) fuel the hypothesis that a larger amount of the ammonia produced by amino acid oxidation is converted to N 2 before being excreted into the surrounding water.…”
Section: Discussionsupporting
confidence: 58%
“…In the nitrogen balance, the percentage of nitrogen that was unaccounted for by retention and excretion was on average 19%–38%, depending on the feeding strategy and dietary protein level. Several previous studies have reported gaps in the nitrogen balance of several fish species, and it thus seems that nitrogen balances cannot always be closed in fish ( Lauff and Wood, 1996 ; Wood, 2001 ; Kajimura et al, 2004 ; Godoy-Olmos et al, 2022 ). Part of the nitrogen gap may be explained by increased fecal nitrogen loss, which we were unable to calculate for our animals as we could not distinguish between uneaten feed pellets and feces during the feeding experiment and was therefore estimated to be 7% based on previous studies in carp.…”
Section: Discussionmentioning
confidence: 99%
“…A microbial oxidative process transforms toxic metabolites such as NH 3 + or NO 2 − into chemical forms less toxic (ammonium or nitrate) to culture organisms through the intervention of nitrifying bacteria [46]. Biofiltration of aquaculture waste consists of substrate and plant systems used for filtration, reduction, and removal of suspended solids [47] macro and micronutrients [48] as well as heavy metals [49]. Where the removal of these components depends on a complex interaction of physical, chemical, biological processes (sedimentation, adsorption, coprecipitation, cation exchange, photodegradation, phytoaccumulation, biodegradation, and microbial activity) and mainly on the type of plant used, as well as its absorption rate [50] in each retention time [51].…”
Section: Biofiltration Of Aquaculture Wastementioning
confidence: 99%
“…The increased concentration of ammonia and its derivatives in the aquaculture environment is one of the riskiest stresses for freshwater fish (Zeitoun et al 2016). Aquaculture utilizes high protein feeds which upon being metabolized yields ammonia as the by-product (Godoy-Olmos et al 2022). In addition, fish faecal matter and other decomposing organic matter increases ammonia concentrations in pond water.…”
Section: Introductionmentioning
confidence: 99%